Sabar dalam Perspektif Hadis: Analisis atas Hadis-hadis dalam Kitab Riyadh al-Shalihin Bab Sabar - Alfiani Zam Zami (Gunung Djati Conference Series, 2022)
Imam Nawawi or Imam Abu Zakaria Yahya Bin Syaraf an-Nawawi is a salaf thinker who produced famous works, one of which is the book of Riyadh Al-Shalihinwhich contains many hadiths in it. This study aims to find out about the analysis of patience contained in the book of Riyadh Al-Shalihinby Imam Zakaria. This study uses a library (Research library) approach and with the same method, the primary data source for this research comes from the book of Riyadh Al-Shalihinwhile the secondary sources are obtained from books and electronic media that are similar and supportive to be used as research objects. The data analysis techniques used are content analysis methods, inductive methods and contextual methods. The findings from this study show that the analysis of patient hadiths in the book of Riyadh Al-Shalihinby Imam Abu Zakaria has a unique discussion compared to other books with almost similar discussions, namely Imam Abu Zakaria grouping the concept of patience into three types, namely: ) patience in obedience to Allah swt, 2) patience from disobedience to Allah swt, and 3) patience in Allah's tests.